2005
DOI: 10.1158/0008-5472.can-05-1799
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of Heat Shock Protein 70 Induction as a Strategy to Increase Antileukemia Activity of Heat Shock Protein 90 Inhibitor 17-Allylamino-Demethoxy Geldanamycin

Abstract: 17-Allylamino-demethoxy geldanamycin (17-AAG) inhibits the chaperone association of heat shock protein 90 (hsp90) with the heat shock factor-1 (HSF-1), which induces the mRNA and protein levels of hsp70. Increased hsp70 levels inhibit death receptor and mitochondria-initiated signaling for apoptosis. Here, we show that ectopic overexpression of hsp70 in human acute myelogenous leukemia HL-60 cells (HL-60/hsp70) and high endogenous hsp70 levels in Bcr-Abl-expressing cultured CML-BC K562 cells confers resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
192
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(210 citation statements)
references
References 50 publications
18
192
0
Order By: Relevance
“…This is closely correlated with MS data on at least three isoforms of Hsp70 proteins (HSPA5, HSPA1B, and HSPA8). This finding is consistent with the results of the in vitro study as well as with earlier studies showing molecular cross-talk between other heat shock family proteins as result of Hsp90 modulation by 17-allylamino,17-demethoxy-geldanamycin (37,38). and establishment of localization (29%) and localized in cytoplasm (70%) and organelle membrane (12%; A and B).…”
Section: Itraq-labeled Ms and Gene Expression Microarray Analysissupporting
confidence: 92%
“…This is closely correlated with MS data on at least three isoforms of Hsp70 proteins (HSPA5, HSPA1B, and HSPA8). This finding is consistent with the results of the in vitro study as well as with earlier studies showing molecular cross-talk between other heat shock family proteins as result of Hsp90 modulation by 17-allylamino,17-demethoxy-geldanamycin (37,38). and establishment of localization (29%) and localized in cytoplasm (70%) and organelle membrane (12%; A and B).…”
Section: Itraq-labeled Ms and Gene Expression Microarray Analysissupporting
confidence: 92%
“…Through its ability to control the activity and stability of many client proteins involved in the oncogenic process, targeting Hsp90 has the potential to affect all the hallmarks of cancer. It is well documented that the Hsp70 family of chaperones have an anti-apoptotic function and targeting the induction of Hsp70 following Hsp90 inhibition sensitized tumor cells to Hsp90 inhibition [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Bagatell et al (11) showed that HSF-1 À/À cells were significantly more sensitive to Hsp90-targeted agents, indicating the potential role of the HSF-1-mediated stress response in 17-AAG resistance. Guo et al (17) showed the importance of Hsp70 in mediating sensitivity to 17-AAG by inhibiting apoptotic signaling in leukemia. This is in agreement with a previous study by Nishimura et al (41) that suggested that Hsp70 is a major factor in determining cell death after heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…Because these proteins are dramatically up-regulated in response to treatment with Hsp90 inhibitors such as GA or 17-AAG (10)(11)(12), their potential involvement in resistance to Hsp90 inhibitors in the clinic has recently gained interest (16). Other studies have shown the protection of cancer cells from 17-AAG-induced death by Hsp70, which is known to be up-regulated in response to Hsp90-directed agents (17). However, other proteins that are up-regulated in an HSF-1-mediated stress response may also contribute to differences in 17-AAG sensitivity.…”
Section: Introductionmentioning
confidence: 99%